Addressing the undergraduate internship challenge in developing countries: A “learning-by-doing” project-based online internship model - Chand, Vijaya Sherry; Deshmukh, Ketan Satish (Education & training (London), 2019)
Purpose: The difficulties higher education institutions in developing countries face in finding adequate and relevant onsite student internship opportunities make a case for online internships. The purpose of this paper is to present an online internship model, developed over a two-year period, which challenged students to engage in learning-by-doing projects that addressed a key barrier in the implementation of ICT policies in public education, the paucity of audio-visual content in local languages. Design/methodology/approach: The design of the model comprised the development of instructional videos by 340 interns, the evaluation of the videos by two interns and their testing by 31 interns through a field experiment using a between-subjects pre-test -- post-test design in 54 schools. The process was repeated the following year with the field experiment replaced by the development of teaching manuals. The changes in reflective learning among 112 of the 119 interns who developed video content in this repeat round were assessed. Findings: The field experiment found that the intern-developed videos improved Mathematics and Science scores among school students but not the attitudes to these subjects. Participation in online internships improved reflective learning. Research limitations/implications: The evaluation of change in reflective learning is based on self-reported measures. Practical implications: The online internship model presented in the paper can address concerns related to inadequate internship opportunities, while addressing gaps in public policy implementation by systems such as education, health and rural development. Originality/value: The paper outlines the design of an online student internship model and a methodology for implementing it. The study indicates the feasibility of a low-cost, large-scale online model of internship.